The Awareness Paradox: Why Better Knowledge of Digital Marketing Boosts Appreciation Without Reducing Skepticism - Shrestha, Sneha; Limbu, Suraj Kurungwang; Shrestha, Shraddha; Basnet, Asmita (NPRC Journal of Multidisciplinary Research, 2025)
Background: Digital marketing has become a cornerstone of modern business strategies, particularly in rapidly digitizing regions like Kathmandu Valley, Nepal. With increasing internet penetration and smartphone usage, businesses leverage digital platforms for advertising, customer engagement, and sales. However, consumer awareness, perceptions, and the societal impact of digital marketing remain understudied in Nepal’s context. This research examines how digital marketing awareness influences individuals’ perceptions, focusing on its positive and negative effects, gender-based differences, and general opinions. Objective: The study aims to (i) Assess the level of digital marketing awareness among Kathmandu Valley residents. (ii) Examine the relationship between awareness and perceived positive/negative impacts. (iii) Evaluate general consumer opinions toward digital marketing. Methods: A quantitative research design was employed, using a structured questionnaire distributed to 200 respondents across various colleges and residential areas in Kathmandu Valley. Data was analyzed using SPSS, incorporating descriptive statistics, Pearson’s correlation, and hypothesis testing. Demographic variables (age, gender, education, internet usage) were examined, and relationships between awareness, perceived impacts, and general opinions were assessed. Findings: (i) Awareness and Positive Impact: A moderate positive correlation (r = 0.345, p < 0.01) was found, indicating that higher awareness leads to more favorable perceptions. (ii) Gender Differences: No significant correlation was observed between gender and awareness, positive/negative impacts, or general opinions (p > 0.05). (iii) Negative Impact: Awareness showed no significant link (p = 0.773) to negative perceptions, suggesting that informed consumers do not necessarily associate digital marketing with harm. (iv) General Opinion: Awareness had no meaningful influence (p = 0.887), implying that other factors shape overall attitudes. Conclusion: The study reveals that while digital marketing awareness enhances positive perceptions, it does not significantly affect negative views or general opinions. Gender plays a negligible role in shaping these perceptions. Businesses should focus on transparency, consumer education, and ethical practices to maximize trust and engagement. Policymakers may consider regulations to address privacy concerns without stifling digital growth. Novelty: This research provides first-hand empirical insights into digital marketing awareness and its societal impact in Nepal, a region underrepresented in global digital marketing literature. Unlike prior studies focused on Western markets, this work highlights localized consumer behavior, offering actionable strategies for Nepalese businesses and regulators.